Diccionario Berlitz plus Español Inglés - Inglés Español
This dictionary has been designed to take account or your practical nedds. Unnecesary linguistic information has been avoided. The entries are listed in alphabetical order regardless of whether the entry word is printed in a single word or in two or more separate words.